Cocrystal habit engineering to improve drug dissolution and alter derived powder properties - Healy, Anne-Marie; O'Connell, Peter (My University, 2016)
Objectives: Cocrystallization of sulfadimidine (SDM) with suitable coformers, such as 4-aminosalicylic acid (4-ASA), combined with changes in the crystal habit can favourably alter its physicochemical properties. The aim of this work was to engineer SDM:4-ASA cocrystals with different habits in order to investigate the effect on dissolution, and the derived powder properties of flow and compaction. Methods: Cocrystals were prepared in a 1:1 molar ratio by solvent evaporation using ethanol (habit I) or acetone (habit II), solvent evaporation followed by grinding (habit III) and spray-drying (habit IV). Key findings: Powder X-ray diffraction showed Bragg peak position was the same in all the solid products. The peak intensity varied, indicating different preferred crystal orientation confirmed by SEM micrographs: large prismatic crystals (habit I), large plate-like crystals (habit II), small cube-like crystals (habit III) and microspheres (habit IV). The habit III exhibited the fasted dissolution rate; however, it underwent a polymorphic transition during dissolution. Habits I and IV exhibited the highest Carr’s compressibility index, indicating poor flowability. However, habits II and III demonstrated improved flow. Spray drying resulted in cocrystals with improved compaction properties. Conclusions: Even for cocrystals with poor pharmaceutical characteristics, a habit can be engineered to alter the dissolution, flowability and compaction behavior.
PUBLISHED
Keywords: Cocrystal, crystal habit, dissolution, flowability, tabletability, wettability; Cocrystal, crystal habit, dissolution, flowability, tabletability, wettability; Nanoscience & Materials; DISSOLUTION RATES; DISSOLUTION TESTING